Odpowiedź :
[tex]log_2x=a[/tex]
[tex]2^a=x[/tex]
[tex]log_3x=b[/tex]
[tex]3^b=x[/tex]
czyli
[tex]2^a=3^b[/tex]
[tex]log_22^a=log_23^b[/tex]
[tex]alog_22=blog_23[/tex]
[tex]a=blog_23[/tex]
[tex]log_23=\frac{a}{b}[/tex]
[tex]log_6x=\frac{log_2x}{log_26}=\frac{a}{log_26}=\frac{a}{log_2(2\cdot3)}=[/tex]
[tex]\frac{a}{log_22+log_23}=\frac{a}{1+log_23}=\frac{a}{1+\frac{a}{b}}=[/tex]
[tex]\frac{a}{\frac{b+a}{b}}=\frac{ab}{a+b}[/tex]
D. ab/(a+b)
[tex]a=\log_2x=\frac{\log_6x}{\log_62}\\b=\log_3x=\frac{\log_6x}{\log_63}\\\frac{1}{a}=\frac{\log_62}{\log_6x}\\\frac{1}{b}=\frac{\log_63}{\log_6x}\\\frac{1}{a}+\frac{1}{b}=\frac{\log_62+\log_63}{\log_6x}=\frac{\log_66}{\log_6x}=\frac{1}{\log_6x}\\\log_6x=\left(\frac{1}{a}+\frac{1}{b}\right)^{-1}\\\log_6x=\frac{ab}{a+b}[/tex]
pozdrawiam